Comparing Diesel Fuels at Various T90 Distillation Temperatures Engine Performance, Vibration and Emissions. - Denoga, Gerald Jo C. (Philippine engineering journal.)
The performance of a Diesel engine was evaluated using fuels with varying T90 distillation temperatures. The T90 distillation temperature is an indicator of the yield of Diesel fuel extracted from crude oil. A higher T90 can translate to better utilization of raw petroleum resources. This experiment verified if high distillation temperatures have any effects on torque, power, specific fuel consumption and emissions. Engine vibrations were also measured and analyzed using accelerometers. Tests were done on a light truck engine connected to a chassis dynamometer.